2019
DOI: 10.1097/md.0000000000017781
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and nonalcoholic fatty liver

Abstract: Background: Opinion regarding whether Helicobacter pylori infection can promote the occurrence and development of nonalcoholic fatty liver (NAFLD) is divided. Therefore, we aimed to assess the exact relationship between H pylori infection and NAFLD by integrating all available data. Methods: The articles about H pylori infection and NAFLD were collected by searching the databases of PubMed, Embase, Web of Science, Scopus, China National Knowledge Infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
0
27
0
3
Order By: Relevance
“…Most of the prior studies have been conducted among Asian populations and further evidence from outside Asia has replicated these findings 8,10 . Meta‐analyses have reported positive associations between H pylori and NAFLD with ORs ranging from 1.14 to 1.53, but noted high heterogeneity among the studies 12‐16 . The heterogeneity may be due to differences in the NAFLD definition and the covariates used for the adjustment in the analyses 12‐16 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most of the prior studies have been conducted among Asian populations and further evidence from outside Asia has replicated these findings 8,10 . Meta‐analyses have reported positive associations between H pylori and NAFLD with ORs ranging from 1.14 to 1.53, but noted high heterogeneity among the studies 12‐16 . The heterogeneity may be due to differences in the NAFLD definition and the covariates used for the adjustment in the analyses 12‐16 .…”
Section: Discussionmentioning
confidence: 94%
“…Meta‐analyses have reported positive associations between H pylori and NAFLD with ORs ranging from 1.14 to 1.53, but noted high heterogeneity among the studies 12‐16 . The heterogeneity may be due to differences in the NAFLD definition and the covariates used for the adjustment in the analyses 12‐16 . In addition, a meta‐analysis from China found a positive association between H pylori infection and risk of obesity among adults, 48 while a systematic review reported that H pylori was associated with insulin resistance 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, other studies reported a positive association between Hp-I and NAFLD, including those of Yu et al [19], Sumida et al [38], Okushin et al [18], Kim et al [10,27], Zhang et al [21], Chen et al [26], Dogan et al [25], Abdel-Razik et al [24], and Kang et al [11]. Noteworthy, there have been five systematic reviews performed with meta-analysis, all of which revealed a positive association between the pathologies of interest [39][40][41][42][43]. Nonetheless, there are studies showing no association between Hp-I and NAFLD [14,15,19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…25 Considering the recent marked reduction in viral hepatitis and the increase in non-alcoholic fatty liver disease (NAFLD) prevalence, 26 the association between H pylori infection and NAFLD has also been evaluated. Four recently published meta-analyses [27][28][29][30] showed a significant association between H pylori infection and NAFLD. This finding was confirmed in a cross-sectional study including 646 patients.…”
Section: Hepatob Iliary D Is E a S E Smentioning
confidence: 99%